The Poor and the Pandemic: COVID-19 - Arati Raut (Journal of Clinical and Diagnostic Research, 2020)
COVID-19 was proven to be a pandemic in early 2020 by the World Health Organisation (WHO). At present, 213 countries have been affected by the COVID-19 pandemic. In the history of global pandemics, COVID-19 has had a major impact on society as it has killed humans, spread human suffering and uprooted the lives of the people. Across the globe, there are 18,705,096 confirmed cases, 11,922,692 recovered cases, 704,385 deaths, and 6,078,019 active cases as of, 5 August 2020. It has affected the world’s economic, social and political status. Poor people belonging to the lower strata of society face more difficulties during pandemics. They are unable to secure their daily bread as well as other basic needs. The impact of COVID-19 on the poor and the role of society have been addressed.